4.6g+3=1.6g+18

Simple and best practice solution for 4.6g+3=1.6g+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.6g+3=1.6g+18 equation:



4.6g+3=1.6g+18
We move all terms to the left:
4.6g+3-(1.6g+18)=0
We get rid of parentheses
4.6g-1.6g-18+3=0
We add all the numbers together, and all the variables
3g-15=0
We move all terms containing g to the left, all other terms to the right
3g=15
g=15/3
g=5

See similar equations:

| d/2+6=9 | | 1/2h=2/5+5 | | 20+3x=-4x-15 | | d/3+9=12 | | -16=3f+-1 | | S+4+2s=47 | | d3+ 9=12 | | 26j=156 | | 24d=144 | | 3w-10=-4 | | m-(-122)=315 | | 4a^2-26a+12=0 | | -3.1x+8=2.9+32 | | m−-122=315 | | 6x+5=7x+6=10x+8 | | 6v-5=19 | | -3.1x=2.9+24 | | 3-7n+6=-12 | | 3(c-6)=21 | | -20.7=-3.2+v/7 | | x+6.96=9.47 | | 4x-4+4x-10=5x+1 | | 5x23=115 | | -11=-7-q/4 | | |4x+4|=2x+8 | | x/10-20=0 | | -30-9h=-5(4h-3) | | 8x-4x+5=2(2x+1)+3 | | 2=4+v/3 | | -4(r+9=65 | | 8−6y=-4y | | -3.1=x/3+4.4 |

Equations solver categories